PRODUCTION OF BIODIESEL FROM JATROPHA CURCAS L OIL - G. SAVITHA; G. R. NAIK (The Bioscan, 2011)
Biodiesel consists of monoalkly esters of long chain of fatty acids produced by transesterification of vegetable oil with alcohol (methanol or ethanol). Biodiesel is an environmentally friend renewable diesel fuel alternative. A bench scale production of biodiesel from Jatropha oil (using methyl alcohol and sodium hydroxide as catalyst) was developed with methyl esters yield of 85%. The produced biodiesel was evaluated as a fuel and compared with petroleum diesel according to its physical and chemical parameters to its physical and chemical parameters such as viscosity, flash point, copper corrosion point and density. The fuel properties of the biodiesel produced were found to be near to that of petroleum diesel. Glycerol was produced as valuable byproduct of the process.